El Excentrico, 1971-05-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
May 20, 1971 [20 de mayo de 1971]. No volume or issue number. Cover has a drawing (possibly an etching) of a man in a charro outfit with the headline "Mariachis! and Queen Coronation Ball" for the American GI Forum Queen Contest and a celebrity appearance by Rafael Medina, also known as El Charro Zacatecano.